Invocation of the GATT security exception after the Russia – Traffic in Transit case - Feret, Gabriela (Wydawnictwo Uniwersytetu Rzeszowskiego, 2021)
This article sets out to examine the national security exception incorporated in an Article XXI(b) (iii) of GATT after a panel issued its final report in the Russia – Traffic in Transit case. This piece focuses on deep analyse of every element of above mention exception as to understand the significancy of each part and the approach taken by the Dispute Settlement Body. In order to do this, the interpretation of this clause in Russia – Traffic in Transit case is used as well as other relevant legal sources and scholars’ articles.

Opracowanie ma na celu analizę zawartego w art. XXI(b)(iii) GATT wyjątku dotyczącego bezpieczeństwa narodowego w świetle ostatniego, końcowego rozstrzygnięcia w sprawie Rosja – działania w zakresie ruchu tranzytowego. Rozważania koncentrują się na ewaluacji poszczególnych elementów klauzuli i ocenie podejścia przyjętego przez Organ Rozstrzygania Sporów. W tym celu w artykule wykorzystano raport wydany w sprawie Rosja – działania w zakresie ruchu tranzytowego, a także źródła prawa dotyczące tej materii oraz wybrane pozycje bibliograficzne.
Keywords: GATT; WTO; Russia – Traffic in Transit case; national security; exception; Article XXI(b)(iii); bezpieczeństwo narodowe; wyjątek; Rosja – działania w zakresie ruchu tranzytowego; art. XXI(b)(iii)